1999
DOI: 10.1002/(sici)1097-0185(19991101)256:3<252::aid-ar5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular gland morphogenesis: Stage-specific expression of TGF-?/EGF, IGF, TGF-?, TNF, and IL-6 signal transduction in normal embryonic mice and the phenotypic effects of TGF-?2, TGF-?3, and EGF-r null mutations

Abstract: Branching morphogenesis of the mouse submandibular gland (SMG) is dependent on cell-cell conversations between and within epithelium and mesenchyme. Such conversations are typically mediated in other branching organs (lung, mammary glands, etc.) by hormones, growth factors, cytokines, and the like in such a way as to translate endocrine, autocrine, and paracrine signals into specific gene responses regulating cell division, apoptosis, and histodifferentiation. We report here the protein expression in embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
107
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 45 publications
12
107
0
5
Order By: Relevance
“…These IGF actions can have also relation with autocrine, paracrine, and with endocrine regulatory mechanisms in different tissues (Pavelić et al, 2007;Vitale et al, 2009). Likewise, also the salivary glands are dependent on factors of growth and endocrine, autocrine, and paracrine signals, which regulate the cell division, apoptosis, and histodifferentiation (Jaskoll and Melnick, 1999). Similar to what was observed in the present study, where the autocrine and paracrine signals also can be involved in the attempt of tissue recovery.…”
Section: Discussionsupporting
confidence: 84%
“…These IGF actions can have also relation with autocrine, paracrine, and with endocrine regulatory mechanisms in different tissues (Pavelić et al, 2007;Vitale et al, 2009). Likewise, also the salivary glands are dependent on factors of growth and endocrine, autocrine, and paracrine signals, which regulate the cell division, apoptosis, and histodifferentiation (Jaskoll and Melnick, 1999). Similar to what was observed in the present study, where the autocrine and paracrine signals also can be involved in the attempt of tissue recovery.…”
Section: Discussionsupporting
confidence: 84%
“…However, media with 10% horse serum was used in these experiments, which contains mitogenic growth factors and makes comparison difficult with our serum-free conditions. The EGFR-null mouse (Jaskoll and Melnick, 1999) has macroscopically normal glands with a reduction of buds/area, suggesting that EGFR regulates SMG branch number in vivo but is not essential for SMG initiation or early branching. An exogenous EGFR ligand is not required for epithelial branching; however, the ECM may contain EGFR ligands or the epithelium may produce an endogenous EGFR ligand.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, epithelial expression was also observed in other branching organs such as salivary glands (30), prostate (8,9), and mammary gland (7). However, IL-6 expression in fetuses was only described during submandibular gland morphogenesis (5,6). In fact, Melnick et al (5) showed a significant increase in IL-6 mRNA with progressive salivary gland development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasized the importance of IL-6 signaling in several processes of branching organs such as embryonic submandibular gland development (5,6), mammary gland remodeling (7), benign and malign prostate growth (8,9), and lung maturation (10).…”
mentioning
confidence: 99%